(NtEORETI^ESKAQ GRAMMATIKA FRANCUZSKOGO QZYKA (B:s (NsINTAKSIS (B: ((NdLQ INSTITUTOW I FAKULXTETOW INOSTRANNYH QZYKOW(B) /s - (NgAK(B, (NwLADIMIR gRIGORXEWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1981)
(NbIBLIOGR(B.: (NS(B. 208s
Keywords: (NfRANCUZSKIJ QZYK s -- (NsINTAKSISs -- (Nu^EBNIKI I POSOBIs